2018
DOI: 10.1080/15459624.2018.1438615
|View full text |Cite
|
Sign up to set email alerts
|

Residential inter-zonal ventilation rates for exposure modeling

Abstract: Residential inter-zonal (e.g., between rooms) ventilation is comprised of fresh air infiltration in and exfiltration out of the whole house plus the "fresh" air that is entering (and exiting) the room of interest from other rooms or areas within the house. Clearly, the inter-zone ventilation rate in any room of interest will be greater than the infiltration/exfiltration ventilation rate of outdoor air for the whole house. The purpose of this study is to determine how much greater the inter-zonal ventilation ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 110 publications
0
4
0
Order By: Relevance
“…In addition to chemical-related model parameters, those describing specific exposure scenarios may also be unknown or highly uncertain. Whenever possible, variability has to be taken into account with respect to exposed populations and occupant characteristics, 123 occupant behaviors, 8,124 and indoor environmental settings 125,126 . Applying Monte Carlo-based approaches to include parameter distributions and addressing certain "special case" scenarios to identify particularly sensitive populations should be part of the application of the framework.…”
Section: Limitations and Conditions Of Usementioning
confidence: 99%
See 2 more Smart Citations
“…In addition to chemical-related model parameters, those describing specific exposure scenarios may also be unknown or highly uncertain. Whenever possible, variability has to be taken into account with respect to exposed populations and occupant characteristics, 123 occupant behaviors, 8,124 and indoor environmental settings 125,126 . Applying Monte Carlo-based approaches to include parameter distributions and addressing certain "special case" scenarios to identify particularly sensitive populations should be part of the application of the framework.…”
Section: Limitations and Conditions Of Usementioning
confidence: 99%
“…In addition to chemical-related model parameters, those parameters describing specific exposure scenarios may also be unknown or highly uncertain. Whenever possible, variability has to be taken into account with respect to exposed populations and occupant characteristics, , occupant behaviors, ,,, and indoor environmental settings. , Applying Monte Carlo-based approaches to include parameter distributions and addressing certain activities to identify high exposure situations should be part of the application of the framework. It has been shown that cooking and cleaning activities greatly enhance the levels of SVOCs in indoor environments compared to background levels. ,, The possibility of aggregate exposures due to certain occupant behaviors and potential consequences for exposed individuals should thus be incorporated in the exposure assessment .…”
Section: A Framework For Predicting Exposure To Indoor Svocsmentioning
confidence: 99%
See 1 more Smart Citation
“…In other cases, a sufficiently dense methodological description might detract from the main objective of a manuscript, and putting procedures [1][2][3] or supporting equations [4] in the supplemental materials makes the manuscript easier to read while providing supporting evidence of the scientific merit of the study to readers. Furthermore, customized software, [5] computer or spreadsheet coding, [6] or data processing techniques [7] used to generate or analyze data may need to be explained in more detail than is reasonable within the body of the manuscript.…”
Section: Why Provide Supplemental Materials?mentioning
confidence: 99%